Let S Get to Work! Government of the Construction of Public Works in Chile at the End of the Colonial Period - Martinez-Barraza, J (CONSEJO SUPERIOR INVESTIGACIONES CIENTIFICAS-CSIC, 2024)
This article studies the aspects involved in the government of the construction of public works in late colonial Santiago de Chile. Based on archives of the Cabildo de Santiago (1740-1810) and Contaduria Mayor significant adjustments to the way of directing the infrastructure factory are demonstrated, whose origin was found in the reformist pinnacle of the Royal Treasury, following the logic of governmental and administrative reorganization of royal treasuries of the Spanish Empire in America. Therefore, it is postulated that the modernization of institutional management was an additional explanatory factor of the construction boom in the period reviewed.